2017
DOI: 10.1186/s12882-017-0542-5
|View full text |Cite
|
Sign up to set email alerts
|

Coping with kidney disease – qualitative findings from the Empowering Patients on Choices for Renal Replacement Therapy (EPOCH-RRT) study

Abstract: BackgroundThe highly burdensome effects of kidney failure and its management impose many life-altering changes on patients. Better understanding of successful coping strategies will inform patients and help health care providers support patients’ needs as they navigate these changes together.MethodsA qualitative, cross-sectional study involving semi-structured telephone interviews including open- and closed-ended questions, with 179 U.S. patients with advanced chronic kidney disease (CKD), either not yet on di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 37 publications
0
31
0
5
Order By: Relevance
“…Previous studies also identified family and friends as a great support system. 45,46 Additionally, participants used comparison and acceptance to manage their difficulties. Possessing the ability to accept difficulties is a powerful coping strategy 47 because it gives older adults a tool to develop new perspectives on life and promotes psychological well-being.…”
Section: Older Adults' Lived Experiencesmentioning
confidence: 99%
“…Previous studies also identified family and friends as a great support system. 45,46 Additionally, participants used comparison and acceptance to manage their difficulties. Possessing the ability to accept difficulties is a powerful coping strategy 47 because it gives older adults a tool to develop new perspectives on life and promotes psychological well-being.…”
Section: Older Adults' Lived Experiencesmentioning
confidence: 99%
“…The observation that patients with FD reported more active coping than patients with chronic pain, could potentially be explained by the fact that in the reference group of patients with chronic pain due to an unknown cause, the pain was localized in the hip and/or knee and was reported to have occurred on at least three occasions over the previous month [ 9 ], whereas not all patients with FD have complaints of pain (58%). Furthermore, no difference in coping behavior was found between FD patients with and FD patients without pain (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…The results of the study showed that patients undergoing hemodialysis have surrendered to God and seek social support as a coping strategy [16]. From other studies, it was indicated that hemodialysis patients do not know what to do unless they undergo hemodialysis routinely [17].…”
Section: The Correlation Between Anxiety and Coping Mechanisms Of Resmentioning
confidence: 97%